LC/MS analysis of stratum corneum lipids: ceramide profiling and discovery - van Smeden, Jeroen; Hoppel, Louise; van der Heijden, Rob; Hankemeier, Thomas; Vreeken, Rob J; Bouwstra, Joke A (Journal of lipid research, 2011)
Ceramides (CERs) in the upper layer of the skin, the stratum corneum (SC), play a key role in the skin barrier function. In human SC, the literature currently reports 11 CER subclasses that have been identified. In this paper, a novel quick and robust LC/MS method is presented that allows the separation and analysis of all known human SC CER subclasses using only limited sample preparation. Besides all 11 known and identified subclasses, a 3D multi-mass chromatogram shows the presence of other lipid subclasses. Using LC/MS/MS with an ion trap (IT) system, a Fourier transform-ion cyclotron resonance system, and a triple quadrupole system, we were able to identify one of these lipid subclasses as a new CER subclass: the ester-linked ω-hydroxy fatty acid with a dihydrosphingosine base (CER [EOdS]). Besides the identification of a new CER subclass, this paper also describes the applicability and robustness of the developed LC/MS method by analyzing three (biological) SC samples: SC from human dermatomed skin, human SC obtained by tape stripping, and SC from full-thickness skin explants. All three biological samples showed all known CER subclasses and slight differences were observed in CER profile.